Exploiting Double Exchange Diels-Alder Cycloadditions for Immobilization of Peptide Nucleic Acids on Gold Nanoparticles - Cadoni, Enrico; Rosa-Gastaldo, Daniele; Manicardi, Alex; Mancin, Fabrizio; Madder, Annemieke (Frontiers in Chemistry, 2020)
The generation of PNA-decorated gold nanoparticles (AuNPs) has revealed to be more difficult as compared to the generation of DNA-functionalized ones. The less polar nature of this artificial DNA system and the associated tendency of the neutral poly-amidic backbone to aspecifically adsorb onto the gold surface rather than forming a covalent bond through gold-thiol interaction, combined with the low solubility of PNAs itself, form the main limiting factors in the functionalization of AuNP. Here, we provide a convenient methodology that allows to easily conjugate PNAs to AuNP. Positively charged PNAs containing a masked furan moiety were immobilized via a double exchange Diels-Alder cycloaddition onto masked maleimide-functionalized AuNPs in a one-pot fashion. Conjugated PNA strands retain their ability to selectively hybridize with target DNA strands. Moreover, the duplexes resulting from hybridization can be detached through a retro-Diels-Alder reaction, thus allowing straightforward catch-and-release of specific nucleic acid targets.